Blood meal identification in the cryptic species Anopheles gambiae and Anopheles coluzzii using MALDI-TOF MS - Tandina, Fatalmoudou (Parasite, 2018)
Matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF MS) has recently emerged in entomology as a technique to identify arthropods and their blood meal source. In this study, female Anopheles gambiae were fed on five host blood sources: ocelot (Leopardus pardalis), binturong (Arctictis binturong), springbok (Antidorcas marsupialis), jaguar (Panthera onca) and Hamadryas baboon (Papio hamadryas), while Anopheles coluzzii were fed on three hosts: dromedary (Camelus dromedarius), Barbary sheep (Ammotragus lervia) and pig (Sus scrofa). We obtained the MS spectra from 240 engorged mosquito abdomens and selected high quality ones from 72 mosquito abdomens to upgrade our home-made database. We excluded from the analysis any spectra of low quality (n = 80), and the remaining 88 specimens were subjected to a blind test analysis against the home-made database. We obtained 100% correct identification of the blood meal source for the specimens collected, 1, 12 and 24 h post-feeding, whereas for the specimens collected 36 h post-feeding, the correct identification rate decreased dramatically. We confirm here that MALDI-TOF MS can be used to identify the blood meal origin of freshly engorged mosquitoes, which opens new perspectives for further studies, including the impact of the mosquito species on blood meal identification.